LEPROSY IN BORDER COUNTRIES IN SOUTH AMERICA: AN ECOLOGICAL STUDY - Keurilene Sutil de Oliveira; Marcos Augusto Moraes Arcoverde; Enrique Jorge Deschutter; Alex Junior da Silva; Adriana Zilly; Reinaldo Antonio da Silva Sobrinho (Universidade Federal do Paraná, 2019)
Objective: to characterize the epidemiological clinical profile and spatial distribution of the incidence of leprosy in border territories of South America. Method: this is an ecological study. The study included the Province of Misiones in Argentina and the Southern Region of Brazil. The population consisted of 10,319 new leprosy cases diagnosed between 2010 and 2016. Results: the state of Paraná was the most endemic, representing 70.2% (n=7.247) of the cases. There was a predominance of multibacillary operational classification (79.8%, n=8,233) and Grade 0 of physical disability (50.6%, n=5,223). In Misiones, 18.9% used a substitution treatment regimen. In the period, a hyperendemic situation was observed in 780 (65.5%) of the studied cities/departments. Conclusion: the study revealed that the regions studied have high endemicity, active transmission and late diagnosis of leprosy. These intertwined trends in the strength of morbidity and recent and persistent transmission of the disease increase the relevance of leprosy as a public health problem in the region.